Persepsi Stakeholder terhadap Fungsi Hutan dalam Upaya Mempertahankan Kawasan Hutan di Desa Kuala Tolam, Kabupaten Pelalawan - Hutasuhut, Ika Lestari; Maryani, Maryani; Allasselcida, Anesha; Agustina, Dinda Tri; Sabri, Erwanda Tri Bintan; Ikhsani, Hanifah; Nugraha, Lefdi Agung; Mohta, Gandhiko; Putra, Agung Kartika (Jurnal Ilmu Ilmu Kehutanan, 2025)
Kuala Tolam Village, Pelalawan Regency, has forest areas and peatland ecosystems that play an important role ecologically, economically, and socially for the community. However, these areas have been experiencing continuous decline and pressure due to industrial activities and land-clearing practices. This condition requires a deeper understanding of stakeholder perceptions of forest functions, as an essential basis for building a commitment to preserve and maintain the remaining forest areas. The purpose of this study is to analyze stakeholder perceptions of forest functions in efforts to maintain forest areas in Kuala Tolam Village, focusing on three aspects: economic, social, and ecological. The research employed both quantitative and qualitative approaches, using interviews with stakeholders who were involved in discussion forums for the formation of commitments to protect forest areas in Kuala Tolam Village. The results show that stakeholder perceptions of forest functions in Kuala Tolam Village fall into the “agree” category across all measured aspects economic, ecological, and social. The positive perceptions of stakeholders regarding forest functions indicate a collective awareness of the importance of forests for life. This awareness serves as social capital for building a shared commitment to safeguarding forest functions and areas.